Élisée Reclus e a Guerra do Paraguai - Hervé Théry; Sébastien Velut (Confins)
Reading the article by Èlisée Reclus "The Paraguayan War", which he published in the Revue des Deux Mondes December 15, 1867, shows that despite its a priori view favorable to Paraguay (compared by him to revolutionary France) makes a penetrating analysis of power relations between the belligerents and anticipates the consequences of the conflict.